Endoscopic management of massive mercury ingestion: A case report. Issue 22 (June 2017) - Zag, Levente; Berkes, Gábor; Takács, Irma F; Szepes, Attila; Szabó, István
Abstract: Rationale: Ingestion of a massive amount of metallic mercury was thought to be harmless until the last century. After that, in a number of cases, mercury ingestion has been associated with appendicitis, impaired liver function, memory deficits, aspiration leading to pneumonitis and acute renal failure. Treatment includes gastric lavage, giving laxatives and chelating agents, but rapid removal of metallic mercury with gastroscopy has not been used. Patient concerns: An 18-year-old man was admitted to our emergency department after drinking 1000 g of metallic mercury as a suicide attempt. Diagnosis: Except from mild umbilical tenderness, he had no other symptoms. Radiography showed a metallic density in the area of the stomach. Intervention: Gastroscopy was performed to remove the mercury. One large pool and several small droplets of mercury were removed from the stomach. Outcomes: Blood and urine mercury levels of the patient remained low during hospitalization. No symptoms of mercury intoxication developed during the follow-up period. Lessons: Massive mercury ingestion may cause several symptoms, which can be prevented with prompt treatment. We used endoscopy to remove the mercury, which shortened the exposure time and minimized the risk of aspiration. This is the first case where endoscopy was used for the management of mercury ingestion.